Clinical and anatomical and pathological diagnosis of metrorragias - Gonzáles del Riego, M. (2015)
This work is based on the study of 562 medical records of patients admitted with metrorragia the Central Military Hospital, which underwent curettage Uterine and where appreciation between clinical diagnosis of admission and histological diagnosis post-operative ago.